Analyse économique du Droit versus Institutionnalisme. Une comparaison « en situation » - Sabine Montagne (Revue de la Régulation)
This paper compares two approaches of law economics concerning the same empirical object - the United States employees savings schemes – on one hand within the framework of mainstream Law and Economics and on the other within the framework of the Theory of the Regulation. These two approaches diverge as regards the way the take into account of politics, understood as conflicting social relationships. Mainstream approach allows avoiding an explicit treatment of politics at the individual level of the particular case. On the contrary, institutionalist habitus produces a political construction of its object of analysis. This "in situation" comparison shows a better capacity of generalization of institutionalist method because of its very dependence in politics.